Melowy. 1, The test of magic - Powell, Cortney Faye (Papercutz, 2018)
As unicorns with special powers, friends Cleo, Electra, Maya, Cora, and Selena study together at a school where they learn to harness their powers and must overcome their fears when the five are assigned a test in a spooky forest.